2022
DOI: 10.3389/fphar.2022.935500
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Serum Haptoglobin and Protein Disulfide-Isomerase A3 in the Screening, Diagnosis, and Staging of Colorectal Cancer

Abstract: Objective: This study aims to explore the clinical significance of haptoglobin (HP) and protein disulfide-isomerase A3 (PDIA3) in human serum in the screening, diagnosis and staging of colorectal cancer (CRC), and to provide novel screening approaches featuring high specificity, sensitivity, and accuracy for early screening and diagnosis of clinical colorectal cancer.Methods: 88, 77, and 36 blood specimens were respectively harvested from colorectal cancer patients, colorectal polyp patients, and normal subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The primary risk factor for CRC is age, with 90% of all diagnosed patients aged over 50 years [ 6 ]. The prognosis of CRC mainly depends on the tumor stage, with the 5-year survival rate decreasing from 91% in the early stage to around 10% in the advanced stage [ 7 ]. The prevalence of colorectal polyps and cancer is significant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary risk factor for CRC is age, with 90% of all diagnosed patients aged over 50 years [ 6 ]. The prognosis of CRC mainly depends on the tumor stage, with the 5-year survival rate decreasing from 91% in the early stage to around 10% in the advanced stage [ 7 ]. The prevalence of colorectal polyps and cancer is significant.…”
Section: Introductionmentioning
confidence: 99%
“…6 The prognosis of CRC mainly depends on the tumor stage, with the 5-year survival rate decreasing from 91% in the early stage to around 10% in the advanced stage. 7 The prevalence of colorectal polyps and cancer is significant. In a study conducted in China, 2,064 colorectal polyp cases were identified among 6,783 eligible participants between March 2018 and December 2019.…”
mentioning
confidence: 99%
“…Cancer remains the main killer worldwide (1)(2)(3)(4). Esophageal cancer is the sixth most commonly diagnosed cancer worldwide and accounts for 450,000 deaths annually (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…However, a considerable proportions of PDIA3 may escape ER retention and get access to other subcellular compartments, potentially exerting non-canonical biological functions (25,26). PDIA3 could also be released in the circulation, serving as a disease biomarker (27). Membrane-associated PDIA3 is an alternative receptor for the active form of 1, 25-dihydroxyvitamin D3 [1,25(OH)2D3], which mediates a rapid (seconds to minutes) ignition of calcium peak (28).…”
Section: Introductionmentioning
confidence: 99%